Analysis of public service satisfaction at puskesmas pakuhaji tangerang - Muqi Mathil Adllil Melsa; Christian Wiradendi Wolor; Marsofiyati, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
At present, government and non-government institutions are developing very rapidly, the government sector is very supportive of the work system, namely public services. This study examines Public Service Satisfaction at the Pakuhaji Health Center, Tangerang Regency. This study aims to understand the extent to which the level of public service satisfaction at the Pakuhaji Health Center, identify factors that influence while receiving services at the Pakuhaji Health Center, and explore efforts to improve these services. Data were collected through interviews, observation, and documentation, with primary and secondary sources providing comprehensive insights. The results of the study show that the level of public service at Pakuhaji Health Center is relatively good, so there is a need for training to improve the quality of public services. Apart from this level, this study highlights satisfaction factors in effective communication between patients and friendly staff and efficient infrastructure. This study seeks to improve public services by measuring Internal Quality Management (IKM) to provide good service to the community.